2022
DOI: 10.1186/s13023-022-02525-0
|View full text |Cite
|
Sign up to set email alerts
|

Children with a rare congenital genetic disorder: a systematic review of parent experiences

Abstract: Background Caring for a child with a chronic disease may be demanding and stressful. When a child has a rare condition, the impact of care on parents is amplified due to the rarity of the diagnosis. In order to address the lack of generalized and synthesized knowledge regarding parents’ experiences of having a child with a rare genetic disorder, and give a holistic picture of these experiences, a systematic review of the available qualitative research was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 85 publications
3
27
0
1
Order By: Relevance
“…Previous studies have established that marriage can be negatively affected when parents have time‐consuming care commitments (Lazzarin et al, 2018; Sevin et al, 2022). However, our findings, aligned with Von Der Lippe et al (2022), revealed that some fathers gained a more robust relationship with their partners. A possible explanation is the strengthened feeling of togetherness, knowing that someone is facing the same stress (Von Der Lippe et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have established that marriage can be negatively affected when parents have time‐consuming care commitments (Lazzarin et al, 2018; Sevin et al, 2022). However, our findings, aligned with Von Der Lippe et al (2022), revealed that some fathers gained a more robust relationship with their partners. A possible explanation is the strengthened feeling of togetherness, knowing that someone is facing the same stress (Von Der Lippe et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings, aligned with Von Der Lippe et al (2022), revealed that some fathers gained a more robust relationship with their partners. A possible explanation is the strengthened feeling of togetherness, knowing that someone is facing the same stress (Von Der Lippe et al, 2022). In addition to changes in fathers' personal relationships, we found that their perceived social role as breadwinners was challenged.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, it is essential to capture the experiences of the patient and caregiver with regard to health care and their psychosocial needs in routine care settings; this is in order to obtain optimal health care and to evaluate current practices [ 12 , 13 , 14 ]. Although the experiences of parents living with a child with SMA have been the focus of several studies [ 15 ], experiences in healthcare from the patient’s or family’s perspective have rarely been assessed in the context of SMA, or have only focused on single aspects, e.g., information or treatment decisions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It reduces off-target delivery beyond that of delivering DNA or RNA-encoded proteins, which rely on the transfection efficacy and the number of gene copies, such as in the ribonucleoprotein delivery for the clustered regularly interspaced short palindromic repeats-associated protein 9 (CRISPR/Cas9) gene editing . Such potential therapeutics offer alternatives against incurable diseases, such as genetic deficiencies of lysosomal enzymes known as lysosomal storage disorders that lead to lysosomal dysfunction. …”
Section: Introductionmentioning
confidence: 99%